Rural health perspectives and experiences - Hussain, Azmal (ICFAI University Press, 2012)
With The Liberalisation Of The Indian Economy And Growing Competition, There Has Been A Shift In The Perception Of The Rural Sector, Particularly From The Point Of View Of Financial Intermediaries. This Sector Is Now Perceived As A Continuous Source Of Savings And An Opportunity For Profitable Deployment Of Funds. Commercial Banks, Nabard, Co-Operative Banks And Regional Rural Banks Have Geared Themselves Up To Cater To This Segment Of The Economy Through Innovative Schemes, Focused Approach, Dedicated Manpower And Training And Educational Programs. Microfinance Institutions And Self-Help Groups Are Also Contributing Significantly To This Process. The Required Financial Architecture Is Being Discussed And Design Of Appropriate Institutions Is Being Debated. The Purpose Of This Book Is To Introduce To The Reader, The Various Financial Intermediaries That Are Involved In Credit Delivery In The Rural Sector. Further, It Deals With The Performance Of The Various Players Involved In Rural Financial Sector Development And Also Takes Stock Of The Various Policies That Have Been Adopted In This Regard. Accordingly, The Book Is Divided Into Two Parts. The First Part Deals With The Various Institutions Involved In Rural Financial Sector Development And Their Performance. The Second Part Deals With Strategies That Can Be Adopted For Improved Credit Delivery.